Talking with patients : keys to good communication - Myerscough, Philip R.; Ford, Michael J. (New York : Oxford University Press, 1996)
A compact source of information on communication skills for physicians and medical students, which includes hints on body language and advice on talking to a variety of specialized patients, including the terminally ill. The practical importance of communication is outlined.
Includes bibliographical references and index
Keywords: Communication; Interpersonal communication; Medical personnel and patient; Physician and patient; Physician-Patient Relations